Spread of mcr-1-carrying Enterobacteriaceae in sewage water from Spain. (10th January 2017) - Ovejero, C. M.; Delgado-Blas, J. F.; Calero-Caceres, W.; Muniesa, M.; Gonzalez-Zorn, B.
Abstract : Objectives: The mobile colistin resistance gene mcr-1 has been identified worldwide in human and animal sources, while its occurrence in the environment is still largely unknown. The aim of this study was to investigate the presence of mcr-1 -harbouring Enterobacteriaceae in water samples obtained from rivers and waste water treatment plants in the area of Barcelona, Spain. Methods: The presence of mcr-1 was detected by PCR. Bacterial identification was performed via MALDI-TOF MS. Resistance to colistin was determined by a broth dilution method. The epidemiological relationship between the positive isolates was assessed with PFGE and ST was determined by MLST. Plasmid characterization was performed by transformation experiments, antimicrobial susceptibility testing and incompatibility group PCR. Results: Thirty MDR isolates bearing mcr-1, 29 Escherichia coli (ST632 and ST479) and 1 Klebsiella pneumoniae (ST526), were identified in sewage from two different waste water treatment plants, whereas the gene was not found in river water. All isolates, including the K. pneumoniae, harboured bla CTX-M-55 and bla TEM-1 . mcr-1 was in all cases associated with an IncI2 plasmid, which only conferred resistance to colistin. mcr-1 was harboured by two predominant E. coli clones that were found in both waste water treatment plants. Conclusions: This study showed a high occurrence of mcr-1 in the sewage of Barcelona, mainly due to the dissemination of two E. coli pulsotypes that are circulating in the population. The presence of mcr-1 in the environment is a cause for concern, and suggests high prevalence of mcr-1 in the community.